2012
DOI: 10.1002/jsfa.5532
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin‐rich red cabbage (Brassica oleracea L.) extract attenuates cardiac and hepatic oxidative stress in rats fed an atherogenic diet

Abstract: Thus, the present study provides the first scientific evidence for a protective role of ARCE against ATH diet-induced hypercholesterolaemia and cardiac and hepatic oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 30 publications
(32 reference statements)
2
36
0
Order By: Relevance
“…These findings suggest that the RCE might possess the ability to reduce reactive oxygen free radicals and improve the activities of hepatic antioxidant enzymes. The present findings are in accordance with a recent study in which the red cabbage methanolic extract has been shown to possess a protective role against atherogenic diet-induced hepatic injury in rats (Sankhari et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…These findings suggest that the RCE might possess the ability to reduce reactive oxygen free radicals and improve the activities of hepatic antioxidant enzymes. The present findings are in accordance with a recent study in which the red cabbage methanolic extract has been shown to possess a protective role against atherogenic diet-induced hepatic injury in rats (Sankhari et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…capitata rubra ) is known for its protective role against cardiac and hepatic oxidative stress in rats fed an atherogenic diet [4], hypocholesterolemic activity in tumour-bearing mice [5], neuroprotective activity in N-methyl-D-aspartate-treated rats [6, 7], paraquat-induced oxidative stress in rats [8], nephroprotective activity in diabetic rats [9], and hepatoprotective activity in carbon tetrachloride-treated rats [10]. Moreover, in vitro polyphenol extract from red cabbage influenced properties of erythrocyte membrane with high concentration of cholesterol [11] and demonstrated high antioxidant activity [1217].…”
Section: Introductionmentioning
confidence: 99%
“…28 This is reported to have anti-oxidant, anti-microbial, gastroprotective, anti-cancer, anti-diabetic, cardioprotective and hepatoprotective effects. [29][30][31][32][33][34][35] Broccoli (Brassica oleracea) contains phenolic compounds and has marked antioxidant activity has been selected and evaluated for its anxiolytic potential. This plant has never been evaluated for their antianxiety potential, therefore it was investigated for its anxiolytic potential.…”
Section: Physicochemical Evaluationmentioning
confidence: 99%